PERAN BEN’S RADIO DALAM MELESTARIKAN BUDAYA BETAWI PADA PROGRAM “BEGAYA” - Shaputra Chandra; Amin Aminudin (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
Radio has an important role in providing information to wide audience, one of them Ben’s Radio who still have the establishment of to preserve betawi culture in the broadcasting. The research aims to determine the role of Ben’s Radio in preserving Betawi culture on the “Begaya” program, and this research uses a qualitative, descriptive approach with data collection techniques in the form of interviews, observations and related documents. The theory used in this study is the theory of production stages. The result of this research suggest that the role of Ben’s Radio seen from the announcer production in the Begaya to preserve betawi culture. The role of the announcer in pre production is doing briefing with producers prior to broadcaster to discuss the theme what will be made for today. Production on stage divide into two the production stage on air and is production stage off air. In the production process on air announcer in control important, broadcast in the process broadcasters do broadcast with using language betawi traditional production on air announcer on stage to engage in events in place by ben’s radio 106,2 FM Jakarta with sponsors and a mc in place by the agency in tourism and culture to fill the they made. The announcer also of an ordinary to make addlibs, jingle advertising, insert the Batavia (discuss about betawi culture in terms of clothing, food, a dance and the myths of betawi culture). In the manner of the announcer preserve betawi culture when production off air by using sadaria clothes and discussing-betawi language. The role after an announcer who do when production is in will evaluate large station manager once a month to discuss the matter or themes that have bring during the production of held.